The relevance of value chain analysis for SMEs : a case study / Sakthi Mahenthiran and Fatimah Bujang - Mahenthiran, Sakthi; Bujang, Fatimah (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
This is a case study undertaken to highlight the importance of undertaking value chain analysis for small and medium sized enterprises in Malaysia. The study uses Porter's (1985) five-force analysis and Riley's (1987) cost driver analysis to highlight the value of reconfiguring the existing value chain of the furniture industry. Major contribution of this study is to highlight the role government subsidies have played in fragmenting this industry and shaping the existing value chain. Additionally, the study speculates as to the reasons why management accounting practices such as activity based cost management are wrongly perceived as being not relevant by the small family owned company that is investigated in this study. Study also highlights some of the weaknesses such as the lack of professional management skills in Small and Medium Enterprises (SMEs) to reconfigure the value chain and improve their profitability.